1995
DOI: 10.1021/j100017a056
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol-OT Reversed Micellar Formation at Low Water-Surfactant Ratio Studied by Synchrotron Radiation Small-Angle X-ray Scattering

Abstract: By using synchrontron radiation small-angle X-ray scattering, we have studied the structure of biologial buffer/ sodium bis(2-ethylhexy1)sulfosuccinate (AOT)/2,2,4-trimethylpentane (isooctane) reversed micelles with varying water-surfactant molar ratio 00 (=[H20]/[AOT]), AOT concentration, and temperature. The scattering data were analyzed by several methods, including a shell modeling. Although in a high (00 range (16 < 00 -= 50) the obtained structural parameters of the AOT reversed micelle and the linear re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
70
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 6 publications
13
70
0
Order By: Relevance
“…In all three simulations, we find that for 15-24 % of the trajectory the RM's forms oligomers, in particular dimers, where the tails of two micelles are in bonding contact for a certain time. This finding agrees well with SAXS experiments 6,7 .…”
supporting
confidence: 93%
“…In all three simulations, we find that for 15-24 % of the trajectory the RM's forms oligomers, in particular dimers, where the tails of two micelles are in bonding contact for a certain time. This finding agrees well with SAXS experiments 6,7 .…”
supporting
confidence: 93%
“…Eastoe et al 27 found a spherical to cylindrical structural transformation of the micelles and back again on the addition of increasing amounts of water; however, the micelles became spherical with the formation of PbS nanoclusters. 14 Hirai et al 24 suggest the presence of a small amount of reverse micellar oligomers and give a length of 12 Å for an AOT molecule, confirming that the shell consists of one layer of AOT molecules.…”
Section: Resultsmentioning
confidence: 95%
“…This corresponds to a spherical radius of 12.1 ( 0.4 Å, which agrees quite well with the results in the literature. 24 The molecular weight and hence the aggregation number can …”
Section: Resultsmentioning
confidence: 99%
“…The simultaneous presence in micellar solution of amorphous clusters and crystalline particles whose d is greater than d p (Fig. 2, curve 1) can be related to the presence in the system of the so-called 'oligomeric' phase [19,25] which represents the associates of interacting micelles. The smaller the micelle size, the greater is their number in such associates.…”
Section: Factors Responsible For the Growth Of Nanoparticlesmentioning
confidence: 99%